1997
DOI: 10.1007/s004600050345
|View full text |Cite
|
Sign up to set email alerts
|

Doubly charged sodium clusters: plasmon response and photoproduction

Abstract: The optical response of doubly charged sodium clusters Na ++ n+2 was measured for n = 20, 40, and 58 valence electrons, for which the jellium model predicts spherical clusters. A new experimental scheme was developed which allows to separate doubly charged clusters of even mass from the singly charged with half the mass. The optical spectra are dominated by a plasmon-like resonance which is blue shifted and narrower than that of the singly charged clusters. The smallest doubly charged cluster observed was Na +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Adding electrons to the cluster (negatively charged clusters) leads to the red shift of the plasmon resonance. These findings are in full agreement with earlier experimental and theoretical data reported in cluster physics, ,− and can be explained within the theory of dynamical screening at surfaces. Neglecting retardation effects, the dipolar plasmon frequency of the nanoparticle is given by , where δ is the position of the dynamically induced screening charges measured with respect to the jellium edge. For positively charged clusters, the electrons are tighter bound in the strong attractive potential well.…”
Section: Absorption Cross Sectionsupporting
confidence: 92%
See 2 more Smart Citations
“…Adding electrons to the cluster (negatively charged clusters) leads to the red shift of the plasmon resonance. These findings are in full agreement with earlier experimental and theoretical data reported in cluster physics, ,− and can be explained within the theory of dynamical screening at surfaces. Neglecting retardation effects, the dipolar plasmon frequency of the nanoparticle is given by , where δ is the position of the dynamically induced screening charges measured with respect to the jellium edge. For positively charged clusters, the electrons are tighter bound in the strong attractive potential well.…”
Section: Absorption Cross Sectionsupporting
confidence: 92%
“…On the contrary, for the negatively charged clusters, the electron density protrudes further away from the cluster boundaries because of the reduced binding so that δ increases and the dipolar plasmon redshifts. 95,96,99 Our results show that charged cluster with excess of electron density located in the surface layer cannot be modeled assuming a bimetallic core−shell nanoparticle with different electron densities and thus different optical response of the core and of the shell. Indeed, in the case of core−shell bimetallic structures, the plasmon modes of the system result from the coupling between the core-localized and shell-localized plasmons.…”
Section: ■ Absorption Cross Sectionmentioning
confidence: 90%
See 1 more Smart Citation
“…It was shown that the value depends sensitively on the excitation mechanism, with ns laser pulses being less favorable, and fs laser pulses as well as fast ion collisions producing significantly lower critical values [28,29]. For Na clusters, the smallest Na cluster with charge state Q = 2 has been observed for Na ++ 10 in experiments with laser pulses [30]. The case of free Na ++ 8 , of interest here, is at the edge of stability.…”
Section: Charge Stabilizationmentioning
confidence: 98%